Efektivitas dan selektivitas beberapa bahan aktif herbisida untuk mengendalikan gulma pada dua varietas tanaman kacang panjang (Vigna sesquipedalis L.) - Wahyu Eko Purnomo; Saifuddin Hasjim (Department of Plant Protection, Faculty of Agriculture, Universitas Jember - Indonesia, 2020)
Field experiments on the effectiveness and selectivity of herbicides use several active ingredients there were Sulfentrazone, Ethyl Pirazosulfuron, and Oxifluorfen with 2 varieties there were Peleton and Kanton tavi. The purpose of the study was to discover the most effective and selective herbicide active ingredients. The study was conducted from February to May 2019. This study used a randomized block design with 7 treatments, namely A (Kontrol), B (Oksifluorfen, peleton), C (Etil pirazosulfuron, peleton), D (Sulfentrazon, peleton), E (Oksifluorfen, kanton tavi), F (Etil pirazosulfuron, kanton tavi), G (Sulfentrazon, kanton tavi). Each treatment was repeated 4 times. The data were analyzed used analysis of variance (ANOVA), further testing used the DMRT test with a 5 % level. The results showed that the application of herbicides made from sulfentrazone, ethyl pirazosulfuron, oxifluorfen in peleton varieties and kanton tavi can suppress weed growth in the research area. The best weed control results were shown by herbicide treatment with sulfentrazone as active ingredient in the kanton tavi variant. The best long bean production results were shown by herbicide treatment with sulfentrazone in peleton varieties. The application of herbicides with active oxifluorfen made no symptoms of phytotoxicity, but decreased the yield of kanton tavi varieties and peleton varieties.